The Ukraine Support Tracker: Which countries help Ukraine and how? - Arianna Antezza; André Frank; Pascal Frank; Lukas Franz; Ekaterina Rebinskaya; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2022)
This paper presents the 'Ukraine Support Tracker', which lists and quantifies military, financial and humanitarian aid to Ukraine in the context of the Russia-Ukraine war. This third version covers government commitments between January 24 and May 10, 2022. We now track support by 37 governments, including all G7 and European Union member countries, plus the support by EU institutions (thus including 38 donors). We also added a section estimating government cost of hosting Ukrainian refugees. Private donations and aid through non-governmental organizations are still not included due to a lack of systematic data. To value in-kind support like military equipment or weapons, we rely on government statements as well as own calculations using market prices. We find significant differences in the scale of support across countries, both in absolute terms and as percent of donor country GDP. In billions of Euros, by far the largest bilateral supporter of Ukraine is the United States, followed by Poland, the United Kingdom, and the EU institutions. In percent of donor GDP, Eastern European countries stand out as particularly generous, and this is even more so once we account for refugee costs.
Additional information: This is the third version (May 18, 2022) of the paper and database. In the coming weeks, we plan to continuously expand, correct, and improve this project. We therefore very much welcome any help to improve the tracker. Please send us feedback and comments to ukrainetracker@ifw-kiel.de. We are greatly indebted to dozens of readers who have sent us helpful comments and suggestions.; More recent version: http://hdl.handle.net/10419/260617
Keywords: F35; F51; H56; H63; H84; H81; 330; International aid; military aid; war; geoeconomics